2013
DOI: 10.1038/nn.3358
|View full text |Cite
|
Sign up to set email alerts
|

Layer V cortical neurons require microglial support for survival during postnatal development

Abstract: Neurons require trophic support during neural circuit formation; however, how the cellular milieu contributes to neuronal survival remains unclear. We found that layer V cortical neurons require support from microglia for survival during postnatal development. Specifically, we found that microglia accumulated close to the subcerebral and callosal projection axons in the postnatal brain. Inactivation of microglia by minocycline treatment or transient ablation of microglia in CD11b-DTR transgenic mice led to inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
556
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 643 publications
(568 citation statements)
references
References 48 publications
8
556
1
3
Order By: Relevance
“…Microglia numbers are elevated during the period of synaptic pruning in development, and following this, microglia numbers then fall to those found in the adult mouse brain (Nikodemova et al, 2015). Microglia during development also control neuronal survival and proliferation (Aarum, Sandberg, Haeberlein, & Persson, 2003; Ueno et al, 2013). Our results show that the elimination and reintroduction of microglia to the aged brain also have marked and parallel effects on neurogenesis, neuronal morphologies/circuitries, and synaptic and behavioral function.…”
Section: Discussionmentioning
confidence: 99%
“…Microglia numbers are elevated during the period of synaptic pruning in development, and following this, microglia numbers then fall to those found in the adult mouse brain (Nikodemova et al, 2015). Microglia during development also control neuronal survival and proliferation (Aarum, Sandberg, Haeberlein, & Persson, 2003; Ueno et al, 2013). Our results show that the elimination and reintroduction of microglia to the aged brain also have marked and parallel effects on neurogenesis, neuronal morphologies/circuitries, and synaptic and behavioral function.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it was shown that microglia-derived insulin-like growth factor 1 was required for survival of layer V cortical neurons during the first week of postnatal life [21]. In addition, deletion of the fractalkine receptor, CX3CR1, which is enriched in microglia versus other resident brain cell types, resulted in delayed maturation of hippocampal synapses and abnormal circuit connectivity in adult mice [22,23].…”
Section: The Role Of Microglia In Cns Developmentmentioning
confidence: 99%
“…18 Likewise, numerous studies have demonstrated microglia's own biological identity including the regulation of synaptic pruning and plasticity, [42][43][44] the spatial distribution of axonal projections, 45,46 and neuronal homeostasis and survival. 47,48 Alternatively, a current hypothesis proposes that microglial reactivity may be stimulated by damaged neurons with deficient signaling, the presence of circulatory plasma molecules in the CNS due to the BBB disruption, and peripheral leukocyte signaling mediated by cytokines after interactions with microbes or their antigens. 24 Major efforts in specifically dissecting the biology of microglia should focused on using epigenomics, comparative transcriptomics, proteomics, and other multidimensional technologies such as computational biology and 2-photon imaging.…”
Section: States Of Existencementioning
confidence: 99%